PENINGKATAN USAHA PEMBENIHAN LELE DUMBO DI DESA NEPEN KABUPATEN BOYOLALI - Wara Pratitis, Erlyana Wida R., (Universitas Negeri Yogyakarta, 2014)
The development of catfish cultivation in Boyolali Regency givesgood prospect for the progress of seeding business in surroundings. Twosamples of catfish seeding groups are Mina Lestari and Mina Mandiri. Bothgroups have been running this business for 3 years and have faced considerableproblems. The problems were (1) the low quality of mother Africancatfish; (2) less maximum seeding of African catfish; (3) limited spawningpools; (4) the woof quality for mother catfish; (5) limited business developmentof each member of both groups. Marketing of catfish seed had goodprospect where the demand of the seed in this village was high enough, eventhe supply could not meet the market.The demand of catfish seed of Kampung Lele cooperative cannot befulfilled for each day due the limited production. Simple business managementmade this business opportunity cannot be explored well. It also affecttedthe business development which ran in slow progress. Based on thoseproblems, the approach methods offered to solve the problems at MinaLestari and Mina Mandiri were: (1) introduction to qualified mother catfish;(2) the improvement of human resource in the technique of catfish seeding;(3) production of alternative woof; (4) increment of permanent spawningpools; (5) improvement in business management.This workshop was given to all members of both groups. The activitiesoffered as the problem solving of the existing problems were all conducted.However, there were some unsolved problems. The problems werein the process of small sized woof for catfish seed and the spawning processwhich often failed probably due to natural factors. The activities which havebeen conducted could help solve the problems faced by Mina Lestari andMina Mandiri. The result could increase the income of the group membersminimal 10% from the prior income. The problem faced in producing pelletwoof was the drying process. In addition, the packaging should be followedup for the sake of the next proposal. Escorting should also be done continuouslyto minimize the problems and to increase the business improvement.